2021
DOI: 10.3389/fpubh.2021.652849
|View full text |Cite
|
Sign up to set email alerts
|

Does Bright Light Counteract the Post-lunch Dip in Subjective States and Cognitive Performance Among Undergraduate Students?

Abstract: The post-lunch dip in alertness and performance was widely experienced during the early afternoon. Taking a short nap was documented as a practical strategy for habitual nappers to counteract the decline of alertness and performance. Yet, it remains unknown whether bright light exposure in the early afternoon working hours could alleviate the performance deficits caused by a post-lunch nap loss for habitual nappers. Seventeen undergraduate students who had a long-term habit of taking a post-lunch nap were assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
0
6
1
Order By: Relevance
“…The PANAS measures two subscales of positive emotion and negative emotion on a five-point likert scale from one (by no means) to five (very high). Cronbach’s alpha obtained is above 70% [ 27 ]. The SAMN-PERELLI has 17 questions and each question is based on a 5-point likert scale (1 = very low, 2 = low, 3 = medium, 4 = high, 5 = very high) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The PANAS measures two subscales of positive emotion and negative emotion on a five-point likert scale from one (by no means) to five (very high). Cronbach’s alpha obtained is above 70% [ 27 ]. The SAMN-PERELLI has 17 questions and each question is based on a 5-point likert scale (1 = very low, 2 = low, 3 = medium, 4 = high, 5 = very high) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this finding, we measured light effects from 07:30 AM to 12:30 PM in our study. However, bright light exposure may also be effective in the afternoon (e.g., during the post-lunch dip 73 ). Fourth, the spectral composition of light was not changed throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is that mental fatigue could reduce the effort of motivation, 12 which increases task difficulty perception sensitivity. The acute effects of daytime light on human working memory have been widely investigated in earlier SL studies; 17,20,61 however, it is questionable whether these results can be directly applied to DL scenarios, as previous studies have shown mixed results in n -back RT. Moreover, whether task difficulty moderates the effect of daytime light on working memory has been noted in the SL field.…”
Section: Discussionmentioning
confidence: 99%
“…19 Based on the conduction path, more and more studies proved that light, especially with high illumination or higher melanopic daylight efficacy ratio results in lower sleepiness and better performance. 20,21 However, the results of exposure to bright or short-wavelength light on alertness, cognition and mood are mixed, which may be affected by mental antecedent conditions. Šmotek et al 22 revealed that short-wavelength light (λ max = 455 nm) during the day may enhance alertness and cognitive performance in healthy adults.…”
Section: Introductionmentioning
confidence: 99%